PUBLIC SERVICE ADMINISTRATION REFORM STRATEGY AT BADUNG REGENCY DRINKING WATER REGIONAL COMPANY - Suacana, I Wayan Gede; Wiratmana, I Nyoman; Sudana, I Wayan (DIA: Jurnal Administrasi Publik, 2024)
The purpose of this research is to find the application of strategic management in the administrative reform of public services at the Regional Water Company Badung Regency. The approach used is a case study, data collection technique used observation, interviews, documentation, and analysis stages of reduction, data presentation, and verification. The SWOT analysis can set six strategic issues and strategies for administrative reform of public services that must be addressed, namely: human resources, administrative leadership, and managerial skills, organizational change and development, public service management information system (SIMPP), systems and procedures, as well as cooperation with the private sector.